Homer1a signaling in the amygdala counteracts pain-related synaptic plasticity, mGluR1 function and pain behaviors - Kuner Rohini; Fu Yu; Tappe-Theodor Anke; Neugebauer Volker (SAGE Publishing, 2011)
Abstract Background Group I metabotropic glutamate receptor (mGluR1/5) signaling is an important mechanism of pain-related plasticity in the amygdala that plays a key role in the emotional-affective dimension of pain. Homer1a, the short form of the Homer1 family of scaffolding proteins, disrupts the mGluR-signaling complex and negatively regulates nociceptive plasticity at spinal synapses. Using transgenic mice overexpressing Homer1a in the forebrain (H1a-mice), we analyzed synaptic plasticity, pain behavior and mGluR1 function in the basolateral amygdala (BLA) in a model of arthritis pain. Findings In contrast to wild-type mice, H1a-mice mice did not develop increased pain behaviors (spinal reflexes and audible and ultrasonic vocalizations) after induction of arthritis in the knee joint. Whole-cell patch-clamp recordings in brain slices showed that excitatory synaptic transmission from the BLA to the central nucleus (CeA) did not change in arthritic H1a-mice but increased in arthritic wild-type mice. A selective mGluR1 antagonist (CPCCOEt) had no effect on enhanced synaptic transmission in slices from H1a-BLA mice with arthritis but inhibited transmission in wild-type mice with arthritis as in our previous studies in rats. Conclusions The results show that Homer1a expressed in forebrain neurons, prevents the development of pain hypersensitivity in arthritis and disrupts pain-related plasticity at synapses in amygdaloid nuclei. Furthermore, Homer1a eliminates the effect of an mGluR1 antagonist, which is consistent with the well-documented disruption of mGluR1 signaling by Homer1a. These findings emphasize the important role of mGluR1 in pain-related amygdala plasticity and provide evidence for the involvement of Homer1 proteins in the forebrain in the modulation of pain hypersensitivity.